O Conhecimento sobre o Programa Saúde Da Família: um olhar sobre a graduação - Leão, Francisco Lázaro; Cruz, Rubens Reis; Santos, James Steffison Souza; Sousa, Ana Luiza Lima (Revista UFG, 2019)
Número especial.